Isolation and Antibacterial Test of Endophytic Bacteria of Avicennia marina Mangroves - Rori, Chindy Achika; Kandou, Febby Ester Fany; Tangapo, Agustina Monalisa (Koli Journal : English Language Education, 2020)
Endophytic bacteria are a source of extracellular compounds such as antimicrobial compounds. Endophytic bacteria and host plants have a symbiotic relationship of mutualism that allows bacteria to produce the same bioactive compounds as those contained in the host plant. This study aims to isolate and test the antibacterial potential of endophytic bacterial Avicennia marina mangroves. The research method used is experimental explorative, isolating bacteria from A. marina mangrove plants and then testing the potential of extracellular enzyme activity from endophytic bacterial isolates. The results of isolation obtained seven isolates of endophytic bacteria from plants A. Marina, the endophytic isolates were able to produce extracellular enzyme activity, namely two isolates had the ability to be antibacterial against Escherichia coli test bacteria.